Intestinal capillariasis: indigenous cases from Chiang Mai and Phayao provinces, Thailand - Benjanuwattar T. (2014)
Two cases of intestinal capillariasis were presented from new locations in northern Thailand, i.e., Phayao and Chiang Mai provinces. Both of them had chronic voluminous diarrhea and malabsorption. It was believed that they acquired the infection indigenously. Both adult worms and their eggs, presented in the feces, were identified as Capillaria philippinensis but with morphological variation. The infection was treated effectively with a prolonged administration of mebendazole.